Herschel-ATLAS: blazars in the SDP field - González-Nuevo, J; Zotti, G; Andreani, P; Barton, E; Bertoldi, F; Birkinshaw, M; Bonavera, L; Buttiglione, S; Cooke, J; Cooray, A; Danese, G; Dunne, L; et al. (2010)
To investigate the poorly constrained sub-mm counts and spectral properties of blazars we searched for these in the Herschel-ATLAS (H-ATLAS) science demostration phase (SDP) survey catalog. We cross-matched 500$μ$m sources brighter than 50 mJy with the FIRST radio catalogue. We found two blazars, both previously known. Our study is among the first blind blazar searches at sub-mm wavelengths, i.e., in the spectral regime where little is still known about the blazar SEDs, but where the synchrotron peak of the most luminous blazars is expected to occur. Our early results are consistent with educated extrapolations of lower frequency counts and question indications of substantial spectral curvature downwards and of spectral upturns at mm wavelengths. One of the two blazars is identified with a Fermi/LAT $γ$-ray source and a WMAP source. The physical parameters of the two blazars are briefly discussed.These observations demonstrate that the H-ATLAS survey will provide key information about the physics of blazars and their contribution to sub-mm counts.